Spinal glial cell line-derived neurotrophic factor infusion reverses reduction of Kv4.1-mediated A-type potassium currents of injured myelinated primary afferent neurons in a neuropathic pain model - Shinoda, Masamichi (Mol Pain, 2019)
High frequency spontaneous activity in injured primary afferents has been proposed as a pathological mechanism of neuropathic pain following nerve injury. Although spinal infusion of glial cell line-derived neurotrophic factor reduces the activity of injured myelinated A-fiber neurons after fifth lumbar (L5) spinal nerve ligation in rats, the implicated molecular mechanism remains undetermined. The fast-inactivating transient A-type potassium current (I(A)) is an important determinant of neuronal excitability, and five voltage-gated potassium channel (Kv) alpha-subunits, Kv1.4, Kv3.4, Kv4.1, Kv4.2, and Kv4.3, display I(A) in heterologous expression systems. Here, we examined the effect of spinal glial cell line-derived neurotrophic factor infusion on I(A) and the expression of these five Kv mRNAs in injured A-fiber neurons using the in vitro patch clamp technique and in situ hybridization histochemistry. Glial cell line-derived neurotrophic factor infusion reversed axotomy-induced reduction of the rheobase, elongation of first spike duration, and depolarization of the resting membrane potential. L5 spinal nerve ligation significantly reduced the current density of I(A) and glial cell line-derived neurotrophic factor treatment reversed the reduction. Among the examined Kv mRNAs, only the change in Kv4.1-expression was parallel with the change in I(A) after spinal nerve ligation and glial cell line-derived neurotrophic factor treatment. These findings suggest that glial cell line-derived neurotrophic factor should reduce the hyperexcitability of injured A-fiber primary afferents by I(A) recurrence. Among the five I(A)-related Kv channels, Kv4.1 should be a key channel, which account for this I(A) recurrence.